(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Now-a-days consumption of plant-based foods, including green leafy vegetables are being considered as part of a healthy diet and importance is given on this by almost all health regulatory bodies of the developed countries. The plant, Emilia sonchifolia belongs of the family, Asteraceae. Nutritional composition of the plant and presence of some essential major elements were analyzed by using standard methods. Freshly collected healthy plants were subjected to assessment for different parameters and nutritional content such as moisture, fat, ash, protein, crude fiber, carbohydrate and energy value as well as probable mineral contents. After nutritional assessment it was revealed that, the contents of total moisture, fat, ash, protein, fiber and carbohydrate were 83.18%, 0.938%, 2.84%, 3.11%, 2.84% and 7.042%, respectively. The total energy content of the plant was 52.624 kcal. The results of the nutritional assessment of E. sonchifolia were near to the popular edible spinach of Amaranthus which contained moisture 81.8 - 83.9%, fat 0.3 - 0.5%, ash 2.8 - 3.6%, protein 4.1 - 4.8%, carbohydrate 4.3 - 5.2%, and energy 47 - 51 kcal. Concentration of macro minerals calcium (Ca), potassium (K), magnesium (Mg) and sodium (Na) was found to be 310, 137, 119 and 55 mg/100g, respectively whereas the concentration of micro minerals iron (Fe), copper (Cu), zinc (Zn), manganese (Mn) and chromium (Cr) was observed as 29, 0.17, 1.21, 1.52 and 0.20 mg/100g, respectively which was between the recommended limit. Bangladesh Pharmaceutical Journal 24(1): 54-60, 2021